ABANDONED PROJECTS-IMPLICATION ON THE STRENGTH OF EXPOSED STEEL AND CONCRETE IN THE SOUTHERN REGION OF NIGERIA (Nigerian Journal of Technology, 2018)
This research is centered on the investigation of the implication of abandonment on the strength of exposed steel and concrete in an abandoned project; as most abandoned project are continued without due consideration to the current strength of the structural members, which may lead to eventual collapse, if the structural members have failed in strength. Six abandoned project sites were investigated: three in Port Harcourt, Rivers state and the other three in Lagos, Lagos state, Nigeria. Thus limiting the investigation to Southern region of Nigeria where the temperature ranges between 23°C and 32°C and precipitation/rainfall ranged between 36mm and 410mm.The Periods of the abandonment ranges from three to thirty-five years. All structural members were cast in-situ. Visual inspections were carried out on site, rebound hammer test was done, concrete samples were cored and steel reinforcement bars were cut from site. Laboratory test and analysis were carried on te cored samples as well as tensile test carried out on the steel samples. Data obtained from both field and laboratory analysis, were analyzed using Excel regression analysis and a model was obtained to help determine the estimated steel strength of exposed steel reinforcement bars after a period of abandonment in the region considered. http://dx.doi.org/10.4314/njt.v37i3.1abandonment, concrete, steel, compressive strength, tensile strength